Percutaneous versus open reduction and fixation for Tillaux and triplane fractures: a multicenter cohort comparison study. Issue 6 (November 2018) - Zelenty, William; Yoon, Richard S.; Shabtai, Lior; Choi, Paul; Martin, Benjamin; Horn, David; Feldman, David S.; Otsuka, Norman Y.; Godfried, David H.
Abstract : The goal of this study was to compare open reduction versus percutaneous fixation of adolescent ankle fractures with regards to the incidence of growth disturbance. We performed a retrospective cohort analysis of adolescent patients with triplane or Tillaux fractures. There was an even distribution of triplane fractures and mean initial displacement between cohorts. Analysis of follow-up radiographs revealed no instances of growth disturbance in the percutaneous fixation group and six in the open reduction group ( P =0.29). Growth disturbance does not pose a significant concern when selecting a surgical approach. Owing to the rarity of these fractures this study was underpowered.